2020
DOI: 10.1128/mbio.02993-20
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Analysis of c-di-GMP Signaling Mechanisms and Biological Functions in Dickeya zeae EC1

Abstract: Dickeya zeae is an important and aggressive bacterial phytopathogen that can cause substantial economic losses in banana and rice plantations. We previously showed that c-di-GMP signaling proteins (cyclases/phosphodiesterases) in D. zeae strain EC1 play a significant role in the bacterial sessile-to-motile transition. To determine whether there is any synergistic effect among these c-di-GMP signaling proteins, we prepared a series of mutant strains by generating consecutive in-frame deletions of the genes enco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 19 publications
(49 citation statements)
references
References 67 publications
(109 reference statements)
1
48
0
Order By: Relevance
“…The intracellular level of c‐di‐GMP in bacterial cells is governed by both diguanylate cyclases (DGCs) and phosphodiesterases (PDEs), which contain GGDEF and EAL (or HD‐GYP) catalytic domains for synthesis and degradation of c‐di‐GMP, respectively (Boehm et al, 2010 ; He et al, 2007 ; Ryjenkov et al, 2006 ; Ryan et al, 2006 ). In Dickeya species, several key c‐di‐GMP metabolic enzymes in modulating motility, biofilm formation, and CWDEs production have been characterized, including two PDEs (EcpB and EcpC) in D. dadantii 3937 (Yi et al, 2010 ) and one DCG (encoded by W909_14945 ) as well as two PDEs (encoded by W909_10355 and W909_14950 ) in D zeae EC1 (Chen et al, 2016 , 2020 ). However, the regulation of these c‐di‐GMP metabolic enzymes has not yet been fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…The intracellular level of c‐di‐GMP in bacterial cells is governed by both diguanylate cyclases (DGCs) and phosphodiesterases (PDEs), which contain GGDEF and EAL (or HD‐GYP) catalytic domains for synthesis and degradation of c‐di‐GMP, respectively (Boehm et al, 2010 ; He et al, 2007 ; Ryjenkov et al, 2006 ; Ryan et al, 2006 ). In Dickeya species, several key c‐di‐GMP metabolic enzymes in modulating motility, biofilm formation, and CWDEs production have been characterized, including two PDEs (EcpB and EcpC) in D. dadantii 3937 (Yi et al, 2010 ) and one DCG (encoded by W909_14945 ) as well as two PDEs (encoded by W909_10355 and W909_14950 ) in D zeae EC1 (Chen et al, 2016 , 2020 ). However, the regulation of these c‐di‐GMP metabolic enzymes has not yet been fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…As a control, overexpression of bifA , a PDE gene participated in c-di-GMP degradation ( Kuchma et al, 2007 ), was unable to restore the biofilm formation of these two mutants ( Figure 6B ). Owing that SiaD-mediated c-di-GMP metabolism has been demonstrated to interconnect with other signaling pathways in PAO1 to coordinate multiple cellular activities ( Colley et al, 2016 ), we additionally overexpressed a DGC W909_14945 from D. zeae EC1 ( Chen Y.F. et al, 2020 ) in the Δ fleS and Δ fleR mutants to ensure that overexpression of the DGC only elevates the intracellular c-di-GMP level.…”
Section: Resultsmentioning
confidence: 99%
“…Elevated c-di-GMP signalling regulates the expression of T3SS genes and pectate lyase (pel) production through YcgR 3937 and BcsA 3937 (Yuan et al, 2015). The findings from our previous study showed that c-di-GMP in D. oryzae EC1 mainly regulates motility and biofilm formation but had no effect on bacterial extracellular enzymes and zeamine production (Chen et al, 2020). In this study, we further showed that elevated cdi-GMP levels did not influence the expression of T3SS genes (Figure S11).…”
Section: Ycgr and Bcsa Interaction With C-di-gmp Is Essential For The...mentioning
confidence: 92%
“…Our previous study showed that the PDE-free mutant 7ΔPDE of D. oryzae EC1, in which all the seven genes encoding PDE enzymes were deleted, with c-di-GMP being highly accumulated in cells, became nonmotile and formed hyperbiofilms (Chen et al, 2020).…”
Section: Deletion Of Ycgr Partially Rescued Bacterial Motility and Bi...mentioning
confidence: 99%